Evaluation of cell culture cytotoxicity of five root canal sealers - Leonardo, Renato de Toledo [UNESP]; Consolaro, Alberto; Carlos, Iracilda Zeppone [UNESP]; Leonardo, Mario Roberto [UNESP] (Wolters Kluwer, 2000)
The cytotoxicity of four calcium hydroxide-based root canal sealers (Sealapex, CRCS, Apexit, and Sealer 26) and one zinc oxide-eugenol-based sealer (Fill Canal) was evaluated microscopically for morphological changes in rat peritoneal macrophages. The least cytotoxic sealer was Fill Canal, followed in increasing order of cytotoxicity by CRCS, Sealer 26, Apexit, and Sealapex. Copyright © 2000 by The American Association of Endodontists.
Keywords: Apexit; bismuth; Calcibiotic Root Canal Sealer; calcium hydroxide; root canal filling material; salicylic acid derivative; sealapex; Sealer 26; zinc oxide; zinc oxide eugenol; animal; cell culture; cell membrane; cell nucleus; cell size; cell vacuole; chromatin; cytoplasm; drug effect; evaluation; nonparametric test; nucleolus; peritoneum macrophage; rat; Animals; Bismuth; Calcium Hydroxide; Cell Membrane; Cell Nucleolus; Cell Nucleus; Cell Size; Cells, Cultured; Chromatin; Cytoplasm; Macrophages, Peritoneal; Rats; Root Canal Filling Materials; Salicylates; Statistics, Nonparametric; Vacuoles; Zinc Oxide; Zinc Oxide-Eugenol Cement